A Forked Staff from Tell Basta - Ashmawy Ali, Aiman (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2024)
This article presents the study of a unique bronze forked staff butt discovered at Tell Basta. It is constructed as an elongated hollow socket ending in two solid prongs, with figurative decorations in-the-round at the junction of the socket and the prongs. The author discusses typology, the decoration represented on the staff, examples of forked staffs in Egyptian art, and their function.